Application of ischaemia‐free liver transplantation improves prognosis of patients with steatotic donor livers – a retrospective study. (7th June 2021) - Chen, Maogen; Chen, Zhitao; Lin, Xiaohong; Hong, Xitao; Ma, Yihao; Huang, Changjun; He, Xiaoshun; Ju, Weiqiang
Summary: The use of steatotic livers in liver transplantation (LT) is controversial. Ischaemia‐free liver transplantation (IFLT) has obvious advantages for the recovery of allograft function. The aim of this study was to examine the effect of liver grafts with steatosis on outcome and the effect of IFLT with steatotic livers. 360 patients with LT were enrolled in this study. Perioperative characteristics and differences in outcome among different grades of steatotic groups, and between the IFLT and conventional LT (CLT) groups were analysed. Occurrence of early allograft dysfunction (EAD; 50%) and primary nonfunction (PNF; 20%) was significantly higher in the severe steatosis group ( P < 0.001 and <0.001, respectively). Survival rate is significantly low in severe steatosis group (3‐year: 60%, P = 0.0039). The IFLT group had a significantly lower occurrence of EAD than the CLT group (0% vs. 60%, P = 0.01). The level of postoperative peak AST, GGT and creatine were significantly lower in IFLT group ( P = 0.009, 0.032 and 0.024, respectively). In multivariable analysis, IFLT and EAD were independent factors affecting postoperative survival. Severe steatotic livers lead to severe complications and poor outcomes in LT. IFLT has obvious advantages for reducing the rate of EAD in LT with steatotic livers.